2011
DOI: 10.1002/prot.23041
|View full text |Cite
|
Sign up to set email alerts
|

Toward the quantum chemical calculation of nuclear magnetic resonance chemical shifts of proteins

Abstract: Despite the many protein structures solved successfully by nuclear magnetic resonance (NMR) spectroscopy, quality control of NMR structures is still by far not as well established and standardized as in crystallography. Therefore, there is still the need for new, independent, and unbiased evaluation tools to identify problematic parts and in the best case also to give guidelines that how to fix them. We present here, quantum chemical calculations of NMR chemical shifts for many proteins based on our fragment-b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

5
91
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 47 publications
(97 citation statements)
references
References 64 publications
(80 reference statements)
5
91
1
Order By: Relevance
“…The omission of these effects in the calculation could contribute to the observed discrepancies between calculated and experimental chemical shift values obtained from solution NMR measurements. 56, 68, 69, 74, 100102 In a previous study a difference of ~5 ppm in experimentally measured isotropic chemical shift values was reported between oxidized and reduced state of cytb 5 . 103 Therefore, the interaction of amide nitrogen with the paramagnetic center of the heme unit could also contribute to the discrepancy.…”
Section: Resultsmentioning
confidence: 90%
See 1 more Smart Citation
“…The omission of these effects in the calculation could contribute to the observed discrepancies between calculated and experimental chemical shift values obtained from solution NMR measurements. 56, 68, 69, 74, 100102 In a previous study a difference of ~5 ppm in experimentally measured isotropic chemical shift values was reported between oxidized and reduced state of cytb 5 . 103 Therefore, the interaction of amide nitrogen with the paramagnetic center of the heme unit could also contribute to the discrepancy.…”
Section: Resultsmentioning
confidence: 90%
“…The range of calculated isotropic chemical shift values is slightly larger (102.7–134.3 ppm) than the range of experimentally determined values (105.3–130.8 ppm), 35 which is still smaller than the range reported for Tfb1/p53 complex in a recent work. 56 Interestingly, in another report 57 it was shown that the use of 6-311g(d) basis set coupled with B3LYP functional produced larger deviations in comparison to experimental results. However, in the present study, the use of larger basis set 6-311+g(2d,p) on 15 N is shown to reduce the variation when compared to the experimental data.…”
Section: Resultsmentioning
confidence: 96%
“…The chemical shifts are extremely sensitive to structural changes. 36 The accurately predicted 13 C chemical shifts 37-39 provide a powerful measure for the protein structure validation. It is likely that a similar correlation between chemical shifts and carbohydrate structures exists as well though such a study has not been carried out systematically.…”
Section: Introductionmentioning
confidence: 99%
“…Rather, one often performs calculations on a protein sub-cluster surrounding the substrate or region of interest using either a purely quantum mechanical (QM) or a hybrid quantum/ classical molecular mechanics (QM/MM) cluster model. Sometimes multiple such QM/MM calculations are performed using a fragment approach (Zhu et al (2012); Frank et al (2011); Tan and Bettens (2013); Gao et al (2014)). …”
Section: Introductionmentioning
confidence: 99%